Analysis of Ectoparasites in Tilapia Fish (Oreochromis Niloticus) in The Riyan Political Harehood Unit (UPR) - Rumondang; Zuhilda Rahmayani Butar-Butar; Ade Corie Yoanda; Mutia Soleh Putri Bb; Moris Gidion Marpaung; Awal Barokah Sinaga; Dewi Utami; Dana Riyadi; Rudi Setiawan; Rizky Handayani (Universitas Islam Lamongan, 2024)
Tilapia is a fishery commodity with high economic value and great demand among farmers. Tilapia fish production in Indonesia recorded an increase from 371 thousand tons in 2021 to 401 thousand tons in 2022, making it one of the largest cultivated fish after shrimp and salmon according to FAO. The advantages of tilapia lie in its high protein content, delicious taste, stable price, ease of cultivation and ability to adapt to new environments and tolerance to low oxygen conditions. However, the main challenge in cultivating tilapia is the attack of non-pathogenic diseases which can cause prolonged stress, decreased body resistance, slow growth and death. Identification of this disease based on water quality is crucial to maintaining fish health and the continuity of cultivation. This study focuses on the identification and analysis of ectoparasites that infect tilapia in the Riyan Community Hatchery Unit (UPR), with the discovery that Dactylogyrus sp. and Trichodina sp. are the two main ectoparasites that affect the health and productivity of fish in that location. Further attention and development of effective control methods are needed to reduce the negative impact of this ectoparasite infection.